Antisemitismo e tecnofobia: il quarto volume dei Quaderni neri di Martin Heidegger (1942-1948) - Fuchs, Christian (Kasparhauser, September 15, 2015)

The Internet, Freedom, and Ideology in the Age of Mass Surveillance - Fuchs, Christian (The Opticon – A Newspaper on Privacy and Surveillance)

Against Divisiveness: Digital Workers of the World Unite! A Rejoinder to César Bolaño and Eloy Vieira - Fuchs, Christian (Television & New Media)

Why we need alternative social media before it is too late - Fuchs, Christian (Connect-World, Global-ICT 2014)

Updated Plan for Use and Foreground. Deliverable D5.3 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Fuchs, Christian; Bellanova, Rocco

Validation Report. Deliverable D5.3 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Fuchs, Christian

Flexible Electronics: Integration Processes for Organic and Inorganic Semiconductor-Based Thin-Film Transistors - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Electronics)
Keywords: Electrical and Electronic Engineering; Computer Networks and Communications; Hardware and Architecture; Signal Processing; Control and Systems Engineering

Silicon Nanoparticles contacted by metal nanogaps for FET applications - Wolff, K; Hilleringmann, Ulrich

Resonant radiation from oscillating higher order solitons - Driben, R.; Yulin, A. V.; Efimov, A. (Optics Express)
We present radiation mechanism exhibited by a higher order soliton. In a course of its evolution the higher-order soliton emits polychromatic radiation resulting in formation of multipeak frequency comb-like spectral band. The shape and spectral position of this band can be effectively controlled by the relative strength of the third order dispersion. An analytical description is corroborated by numerical simulations. It is shown that for longer pulses the described effect persists also under the action of higher order perturbations such as Raman and self-steepening.

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Yulin, A. V.; Driben, R. (Optics Letters)
The effect of mutual interactions between dark solitons and dispersive waves is investigated numerically and analytically. The condition of the resonant scattering of dispersive waves on dark solitons is derived and compared against the results of the numerical simulations. It is shown that the interaction with intense dispersive waves affects the dynamics of the solitons by accelerating, decelerating, or destroying them. It is also demonstrated that two dark solitons can form a cavity for dispersive waves bouncing between the two dark solitons. The differences of the resonant scattering of the dispersive waves on dark and bright solitons are discussed. In particular, we demonstrate that two dark solitons and a dispersive wave bouncing in between them create a solitonic cavity with convex “mirrors,” unlike the concave “mirror” in the case of bright solitons.

Investigation on joint characteristics of laser beam welded press hardenable ultra-high strength steels with ferritic-martensitic and martensitic microstructure - Janzen, V.; Meschut, G.; Dahmen, M.; Poprawe, R.; Lindner, S.; Wagener, R.; Melz, T. (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Die Manipulation der Bedürfnisse. Zum Verhältnis von Kritik und Geist der Werbung - Hälterlein, Jens (Sociologia Internationalis. Europäische Zeitschrift für Kulturforschung)

Die Regierung des Konsums - Hälterlein, Jens

Vectorial self-accelerating beams - Meier, Torsten; Driben, R.; Konotop, V.V. (European Conference on Lasers and Electro-Optics - European Quantum Electronics Conference)
The discovery of Airy waves, in the context of solutions to the linear Schrödinger equation [1], inspired extensive research for self-accelerating waves in optical settings [2-6]. Fascinating self-accelerating, self-healing light beams propagating along the bending trajectories can manifest themself in the spatial and the temporal domains and are promising for a large variety of potential applications.

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Creation of vortices by torque in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Meier, Torsten; Malomed, Boris A. (Scientific Reports)
Recently, a new class of nonlinear systems was introduced, in which the self-trapping of fundamental and vortical localized modes in space of dimension D is supported by cubic self-repulsion with a strength growing as a function of the distance from the center, r, at any rate faster that rD. These systems support robust 2D and 3D modes which either do not exist or are unstable in other nonlinear systems. Here we demonstrate a possibility to create solitary vortices in this setting by applying a phase-imprinting torque to the ground state. Initially, a strong torque completely destroys the ground state. However, contrary to usual systems, where the destruction is irreversible, the present ones demonstrate a rapid restabilization and the creation of one or several shifted vortices orbiting the center. For the sake of comparison, we show analytically that, in the linear system with a 3D trapping potential, the action of a torque on the ground state is inefficient and creates only even-vorticity states with a small probability.

Non-coaxial vortices in two-component Bose-Einstein condensates: Persistent precession and nutation - Meier, Torsten; Driben, R.; Konotop, V.V. (arXiv preprint arXiv:1505.04113)
It is demonstrated that a two-component Bose-Einstein condensate (BEC) with all-repulsive inter-atomic interactions loaded into a radially symmetric harmonic trap supports robust non-coaxial vortices with approximately orthogonal vortex lines in each of the components. These cross vortices are excited from the linear modes by a sudden switch-on of the nonlinearity (via Feshbach resonance) and are characterized by persistent dynamical regimes of precession with nutation, resembling the motion of a rigid body. The obtained dynamics can be understood qualitatively on the basis of a simple mechanical model.

Psalmen ohne Worte. Ein instrumentales Zwischenspiel aus den letzten zwei Jahrhunderten - Schroeter-Wittke, Harald (Theologie des Psalters. Günter Bader zum 70. Geburtstag)

Zukunft als Verfall? Transformationsprospekte von Kirche angesichts der Transformationen von Gesellschaft - Schroeter-Wittke, Harald (Praktische Theologie)

Aalaiki'ssalaam. Zum 60. Geburtstag von Naji Hakim - Schroeter-Wittke, Harald (Praktische Theologie)